Self-cleaving guide RNAs enable pharmacological selection of precise gene editing events in vivo - Amita Tiyaboonchai; Anne Vonada; Jeffrey Posey; Carl Pelz; Leslie Wakefield; Markus Grompe (Nature Communications, 2022)
Here, authors show that precise integration of an rAAV vector into a chromosomal target locus results in expression of a self-cleaving guide RNA. This recombination event creates genetic resistance to a hepatotoxic compound and enables in vivo expansion of gene-edited hepatocytes using a selection drug.